Overcoming origin-based preferences by selecting skilled immigrants? Preferences in immigrants' national origin and social class in Quebec. - Bilodeau, Antoine; Gagnon, Audrey (Journal of Ethnic & Migration Studies, 2024)
Although most liberal democracies have abandoned preferences for national origins in immigrant selection policies, large segments of the local populations continue to prefer immigrants that they perceive to be of similar cultural, religious, and ethnic backgrounds as them. What remains unknown is whether governments can count on the promotion of successful economic integration to ensure acceptance of the greater ethnocultural and religious diversity of immigrants that now settles in host-countries through what has been identified as building a middle-class nation. Relying on an original survey experiment of 2400 respondents in Quebec, we compare reactions to immigrants of different professional status and two national origins (France and Algeria) to investigate if certain types of economic immigration can reduce origin-based preferences. Our results show that origin-based preferences shared by majority group members can be attenuated, but not eliminated by selection based on social class. That said, expectations that immigrants will contribute to Quebec's economy translate into greater acceptance of immigrants of all national origins and social classes.